Efektifitas Penguraian Sampah Rumah Tangga Menggunakan Larva Black Soldier Fly dengan Variasi Substrat - Dea Febrica Ervina; Yayok Suryo Purnomo; Syadzadhiya Qothrunada Zakiayasin Nisa (Jurnal Serambi Engineering, 2024)
The increase in waste generation in Indonesia in 2023 has reached 17,027,843.29 tons/year. The largest source of waste is categorized as food waste composition originating from household activities with 3997.2 tons/year or a percentage of 38.4%. One approach that can overcome this problem is by using Black Soldier Fly larvae. These larvae can obtain energy and nutrients from vegetable scraps, food scraps, animal carcasses, domestic waste and liquid waste as their food source. This research aims to analyze the effectiveness of decomposing household waste using BSF larvae and the growth of BSF larvae. This research involves a variety of larval feed from household waste that has not been cooked or has undergone a cooking process as well as waste that contains fiber, carbohydrates and is high in protein. The results showed that BSF larvae with a combination of boiled water spinach, catfish head waste, and stale rice (H1) had the highest reduction value, reaching 90%. Meanwhile, the highest weight gain for BSF larvae was on the substrate of boiled water spinach, catfish head waste, stale rice, and vinegar solution (H2) with an ECD value of 69%